eIF4A controls germline stem cell self-renewal by directly inhibiting BAM function in the Drosophila ovary. - Shen, R.; Weng, C.; Yu, J.; Xie, T. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Stem cell self-renewal is controlled by concerted actions of extrinsic niche signals and intrinsic factors in a variety of systems. Drosophila ovarian germline stem cells (GSCs) have been one of the most productive systems for identifying the factors controlling self-renewal. The differentiation factor BAM is necessary and sufficient for GSC differentiation, but it still remains expressed in GSCs at low levels. However, it is unclear how its function is repressed in GSCs to maintain self-renewal. Here, we report the identification of the translation initiation factor eIF4A for its essential role in self-renewal by directly inactivating BAM function. eIF4A can physically interact with BAM in Drosophila S2 cells and yeast cells. eIF4A exhibits dosage-specific interactions with bam in the regulation of GSC differentiation. It is required intrinsically for controlling GSC self-renewal and proliferation but not survival. In addition, it is required for maintaining E-cadherin expression but not BMP signaling activity. Furthermore, BAM and BGCN together repress translation of E-cadherin through its 3' UTR in S2 cells. Therefore, we propose that BAM functions as a translation repressor by interfering with translation initiation and eIF4A maintains self-renewal by inhibiting BAM function and promoting E-cadherin expression.